Friedrich von Hausen Inquiries Into His Poetry - Bekker, Hugo (UNC Studies in the Germanic Languages and Literatures, 1977)
The author casts new light on Hausen's lyrics by often favoring the manuscript readings. In the readings, irony emerges as a leading poetic device, as does the element of "Spiel". Questions arise regarding such concepts as "Gottesdienst", "Frauendienst", and "hohe Minne". Attrition is discussed as the possible motivation behind the "persona"'s decision to take the cross.